PENGARUH SERVICE QUALITY, PERCEIVED VALUE, TRUST, CUSTOMER SATISFACTION TERHADAP LOYALTY DI PATUNA TOUR & TRAVEL - Prabowo, Arif; Mardhiyah, Dien (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
This study examines the effect of service quality, perceived value, trust, and customer satisfaction on loyalty in Patuna Tour & Travel. The data analysis technique used in this study uses a partial least square. The sample used was 360 individual respondents or ex-pilgrims who had, at least twice, used the services of Patuna Tour & Travel in carrying out the Umrah pilgrimage. The results showed that service quality has a positive effect on perceived value, service quality has a positive effect on customer satisfaction, service quality has a positive effect on trust, perceived value has a positive effect on customer satisfaction, perceived value has a positive effect on trust, customer satisfaction has a positive effect on trust, trust has a positive effect positive on loyalty and customer satisfaction does not affect loyalty